Evolution of olfactory receptor genes in the human genome - Niimura, Yoshihito (National Academy of Sciences, 2003)
Olfactory receptor (OR) genes form the largest known multigene family in the human genome. To obtain some insight into their evolutionary history, we have identified the complete set of OR genes and their chromosomal locations from the latest human genome sequences. We detected 388 potentially functional genes that have intact ORFs and 414 apparent pseudogenes. The number and the fraction (48%) of functional genes are considerably larger than the ones previously reported. The human OR genes can clearly be divided into class I and class II genes, as was previously noted. Our phylogenetic analysis has shown that the class II OR genes can further be classified into 19 phylogenetic clades supported by high bootstrap values. We have also found that there are many tandem arrays of OR genes that are phylogenetically closely related. These genes appear to have been generated by tandem gene duplication. However, the relationships between genomic clusters and phylogenetic clades are very complicated. There are a substantial number of cases in which the genes in the same phylogenetic clade are located on different chromosomal regions. In addition, OR genes belonging to distantly related phylogenetic clades are sometimes located very closely in a chromosomal region and form a tight genomic cluster. These observations can be explained by the assumption that several chromosomal rearrangements have occurred at the regions of OR gene clusters and the OR genes contained in different genomic clusters are shuffled.